Pengaruh Transformasi Digital dan Bisnis Online Terhadap Pola Perilaku Masyarakat dalam Menggunakan M-Banking Syariah: Studi Kasus pada Masyarakat Martubung - Nadya Fardha Lubis; Riyan Pradesyah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study was to determine the effect of digital transformation and online business on the behavior patterns of the Martubung community in using Islamic M-Banking. Where at this time, many people are worried about using M-banking, because many people are exposed to fraud in using M-banking. Therefore, the study wanted to test the variables of digital transformation and online business development in influencing the interest of the Martubung community in using M-Banking. The sample used in the study amounted to 100 people with the characteristics of sharia M-Banking users. The data obtained is processed using the SPSS 27 application, using multiple linear regression methods. The results obtained that by farsiap or t test, the digital transformation variable affects the behavior patterns of the martubung community using sharia M-Banking. Then the online business variable affects the behavior patterns of the Martubung community using sharia M-Banking. Simultaneously, the Digital Transformation and Online Business variables affect the behavior patterns of the martubung community using sharia M-Banking, amounting to 69.1% and the remaining 30.9% is influenced by other variables not included in the study.